Impacts of accessing extension on agricultural production profit: Empirical evidence from the Viet Nam Access to Rural Households Survey - Do Huy Thiep; Nguyen Thi Cam Nhung (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper aims to evaluate the impact of accessing agricultural extension on households' agricultural profit. Results from pooled cross-sectional data show that each additional time of access is associated with a 15.5 per cent increase in agricultural profit. However, this relation is not linear and if it exceeds 6 times, it will eventually cause more harm than good. We also construct a household and time-fixed effect model to eliminate the effect of unobserved factors. The local extension service impact on agricultural profit is 15.2 per cent for 2010-12; 19.8 per cent for 2012-14 and 25.5 per cent for 2014-16.
Keywords: A16; C31; C33; 330; Agricultural extension; fixed effects